Truth and salsa - Keep, Linda Lowery. (Peachtree, 2006)
Having moved temporarily from Michigan to live with her grandmother in Mexico, twelve-year-old Hayley tries to sort out her feelings about her parents' separation while also helping some townsmen who have run into trouble while working in the United States.